2023
DOI: 10.1200/jco.2023.41.16_suppl.e16084
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of perioperative chemotherapy combined with tislelizumab and trastuzumab for HER2-positive resectable gastric/gastroesophageal junction cancer (GC/EGJC): Preliminary results of a phase 2, single-arm trial.

Abstract: e16084 Background: Recently, immunotherapy combined with trastuzumab and chemotherapy have been recommended by the clinical guidelines of many countries as the first-line treatment for advanced HER2-positive G/GEJ adenocarcinoma. Combining chemotherapy with tislelizumab and trastuzumab in the neoadjuvant/adjuvant setting may benefit patients with locally advanced, resectable HER2-positive GC/GEJC. Methods: This study is a multicenter, single-arm, open-label phase 2 study (NCT04819971). Patients with histologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Of these, 16 patients underwent D2 resection, with 9 (56.3%) achieved MPR, including 5 (31.3%) with pCR (ypT0N0M0), and the ORR was 77.3% (Li et al, 2022). Another similar single-arm, phase 2 trial (NCT04819971) demonstrated a pCR rate of 42.9% (3/7) and an MPR rate of 57.1% (4/7) with the perioperative treatment of tislelizumab, trastuzumab and DOS (Zhao et al, 2023). These trials suggest that the triple combination therapy is promising, with encouraging pCR and an acceptable toxicity profile.…”
Section: Icis In Combination With Targeted Therapymentioning
confidence: 99%
“…Of these, 16 patients underwent D2 resection, with 9 (56.3%) achieved MPR, including 5 (31.3%) with pCR (ypT0N0M0), and the ORR was 77.3% (Li et al, 2022). Another similar single-arm, phase 2 trial (NCT04819971) demonstrated a pCR rate of 42.9% (3/7) and an MPR rate of 57.1% (4/7) with the perioperative treatment of tislelizumab, trastuzumab and DOS (Zhao et al, 2023). These trials suggest that the triple combination therapy is promising, with encouraging pCR and an acceptable toxicity profile.…”
Section: Icis In Combination With Targeted Therapymentioning
confidence: 99%